2018
DOI: 10.1177/1533034618766792
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a Deformed Tumor Based on Fiducial Marker Registration: A Computational Feasibility Study

Abstract: Interstitial photodynamic therapy has shown promising results in the treatment of locally advanced head and neck cancer. In this therapy, systemic administration of a light-sensitive drug is followed by insertion of multiple laser fibers to illuminate the tumor and its margins. Image-based pretreatment planning is employed in order to deliver a sufficient light dose to the complex locally advanced head-and-neck cancer anatomy, in order to meet clinical requirements. Unfortunately, the tumor may deform between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, the difference in DVHs (from errors in fibers location) must be calculated for specific optical properties. In another study, we evaluated the impact of tumor deformation on the DVHs . Since LAHNC are not likely to deform or shift significantly, we ran simulations to assess the impact of 10% deformation on the DVHs and found that this level of deformation will have minor effects (0.5–3%) on the actual DVH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the difference in DVHs (from errors in fibers location) must be calculated for specific optical properties. In another study, we evaluated the impact of tumor deformation on the DVHs . Since LAHNC are not likely to deform or shift significantly, we ran simulations to assess the impact of 10% deformation on the DVHs and found that this level of deformation will have minor effects (0.5–3%) on the actual DVH.…”
Section: Discussionmentioning
confidence: 99%